2015
DOI: 10.1037/gdn0000034
|View full text |Cite
|
Sign up to set email alerts
|

Group interaction sustains positive moods and diminishes negative moods.

Abstract: The social interactions of task groups were investigated for their influences on member moods. Initially, participants’ received an induction of positive, negative, or neutral moods via listening to music that continued throughout the experimental session. Moods were measured after the induction. Students then made decisions on four choice dilemmas alone or as members of a four-person group. Subsequently, positive and negative moods were again measured. Positive moods of participants who worked with other grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 39 publications
6
23
0
Order By: Relevance
“…In addition to the previously mentioned work that documented declines in negative affect following group involvement (Park & Hinsz, 2015), research shows that perceptions of threat and the difficulty of challenges also decrease in the presence of familiar or similar others. For example, compared with when alone, (a) potential foes appear physically smaller and less muscular when male raters are with a group of friends (Fessler & Holbrook, 2013); (b) in the mere presence of a friend or when simply activating mental images of an existing friendship, challenges are perceived to be more manageable (Schnall, Harber, Stefanucci, & Proffitt, 2008); (c) when holding a spouse's hand, neural responses to experimentally induced threat are reduced (Coan, Schaefer, & Davidson, 2006); and (d) when people receive positive social support from others, less experimentally induced pain is felt (Brown, Sheffield, Leary, & Robinson, 2003).…”
Section: Group Involvement Should Decrease Inhibitions and Avoidance mentioning
confidence: 79%
See 1 more Smart Citation
“…In addition to the previously mentioned work that documented declines in negative affect following group involvement (Park & Hinsz, 2015), research shows that perceptions of threat and the difficulty of challenges also decrease in the presence of familiar or similar others. For example, compared with when alone, (a) potential foes appear physically smaller and less muscular when male raters are with a group of friends (Fessler & Holbrook, 2013); (b) in the mere presence of a friend or when simply activating mental images of an existing friendship, challenges are perceived to be more manageable (Schnall, Harber, Stefanucci, & Proffitt, 2008); (c) when holding a spouse's hand, neural responses to experimentally induced threat are reduced (Coan, Schaefer, & Davidson, 2006); and (d) when people receive positive social support from others, less experimentally induced pain is felt (Brown, Sheffield, Leary, & Robinson, 2003).…”
Section: Group Involvement Should Decrease Inhibitions and Avoidance mentioning
confidence: 79%
“…Research has shown that even short-lived, ad hoc workgroups have the propensity to sustain positive feelings in members who are working on a task. In one study (Park & Hinsz, 2015), mood was assessed before and after the completion of a decision-making task. Some participants completed the task alone, while others completed the task as a group.…”
Section: Group Involvement Should Increase Approach Motivationmentioning
confidence: 99%
“…It should be noted that PSI may evoke a shared feeling of an elevated mood,[ 47 48 ] which might benefit the patients with some physical effects, including decreased pain. [ 49 ] Psychologically speaking, the intimate interactors (e.g., friends) in a social context tend to mimic smiles and empathize with the expressed happiness.…”
Section: Discussionmentioning
confidence: 99%
“…The former underlines emotion and the latter does cognition (Nozaradan, Peretz, & Mouraux, 2012;Lidji, Palmer, Peretz et al, 2011). People's emotion standards roughly include subjective experience, physiological arousal, brain activation, facial expression, behavior disposition and emotional regulation (Park & Hinsz, 2015). Methods for measuring how the music infects human emotions include subjective reporting, facial expression measurement technology, psychophysiological measurement (heart rate, respiration rate, and skin response) and central nervous system measurement.…”
Section: Relevant Factors and Theories Of Emotional Contagionmentioning
confidence: 99%